SIBERKREASI KOMINFO SEBAGAI SALAH SATU PROGRAM GERAKAN NASIONAL LITERASI DIGITAL - RUBY RACHMADINA, (2020)
SIBERKREASI KOMINFO AS ONE OF THE DIGITAL LITERACY NATIONAL MOVEMENT PROGRAMS By: RUBY RACHMADINA ABSTRACT Negative content that develops in various kinds of social media is one of the factors that motivates the Ministry of Communication and Information to do digital literacy creation, digital literacy activities carried out to educate the public how to be aware of digital threats such as hoaxes, cyber bullying and so on. The obligation of the Ministry of Communication and Information to titrate the community, aims at being able to select and sort out information that is circulating outside and the community is able to use social media or anything that is closely related to the digital world for things that are positive and productive. This research method uses a qualitative approach. The results of the research refer to do can be known as follows: The stages of Digital Literacy Literacy activities carried out are divided into three stages, starting from the planning stage, the implementation stage and the evaluation stage. The three speakers who have participated in the digital literacy activities of cyber creation have understood the ability of new media literacy introduced by Jenkins et al in the theory of new media literacy. All three speakers have understood the ability to play, simulation ability, performance ability, appropriation ability, collective intelligence ability, judgment ability. Keywords: Digital Literacy, Media Literacy, Social Media, Negative Content